1988
DOI: 10.3354/meps045081
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense in a scyphomedusa

Abstract: ABSTMCT: The scyphozoan Stomolophus meleagris, when disturbed (held in a container), discharges a sticky mucus. Toxins released into the mucus and water kill some fish and crustaceans and can immediately alter fish behavior, but did not affect a crab predator of S. meleagris. The mucus contains discharged and undischarged nematocysts. The toxins in the mucus are probably associated with these nematocysts. In the field. S. meleagris subjected to a simulated small predator bite released clouds of nematocysts whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
51
1
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 13 publications
2
51
1
2
Order By: Relevance
“…Although associations between crabs and medusae are apparently not species-specific, three species of Libinia appeared mainly with four Rhizostomeae jellies (eight records). These results agree with this work where L. ferreirae was found on Rhizostomeae only, which are usually larger and less harmful medusae, possibly due to the presence of epidermal cnidae only in the oral arms (tentacles are absent in (SHANKS & GRAHAM 1988). Cnidae resistance in L. ferreirae can also be noted by the high frequncy of sea anemones found on the adults living outside the medusae.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although associations between crabs and medusae are apparently not species-specific, three species of Libinia appeared mainly with four Rhizostomeae jellies (eight records). These results agree with this work where L. ferreirae was found on Rhizostomeae only, which are usually larger and less harmful medusae, possibly due to the presence of epidermal cnidae only in the oral arms (tentacles are absent in (SHANKS & GRAHAM 1988). Cnidae resistance in L. ferreirae can also be noted by the high frequncy of sea anemones found on the adults living outside the medusae.…”
Section: Discussionsupporting
confidence: 82%
“…With respect to the type of association, we consider it probably only beneficial to the crab (CORRINGTON 1927, VAZ FERREIRA 1972, ZAMPONI 2002. The association could even be harmful to L. lucerna, if the crab feeds on parts of its host tissue, a trend not observed in this study, but reported for L. dubia associated with A. aurita (Linnaeus, 1758) and S. meleagris, respectively by JACHOWSKI (1963) and SHANKS & GRAHAM (1988).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Although some macro-holoplankton might have reduced susceptibilities to predators because of small body size, transparency, diel vertical migration, exploitation of the sea surface, spines, or shells (Cheng 1975;Gliwicz 1986;Lalli and Gilmer 1989;McFall-Ngai 1990;Hamner 1996;McClintock et al 2001), others have no apparent defenses and are sluggish, are highly pigmented, and have soft bodies. Because species lacking obvious defenses persist in the plankton, it has been hypothesized that chemical defenses might be common among macro-holoplankton (Shanks and Graham 1988;McClintock et al 1996). Although chemical defenses have been found in a few macro-holoplankton (Shanks and Graham 1988;Bryan et al 1995), it is unclear whether these cases are unusual exceptions or the norm.…”
mentioning
confidence: 99%
“…Feeding-deterrent properties have been detected in two other groups of zooplankton. Shanks and Grahm (1988) reported on chemical defense in the scyphomedusa Stomolophus meleagris; Galt (unpubl. ) reported that the mucus house, but not the body, of the larvacean Oikopleura Zongicauda deters feeding in the reef fish DacyZZyus albisella and Abudefduf abdominalis.…”
mentioning
confidence: 99%